Strategic Analysis of the Need for Policy Strengthening Quality Improvement of Graduates of Syekh Ali Hasan UIN Ahmad Addary Padangsidimpuan - Buyung Saroha Nasution; Mulyono (AMUYA: JOURNAL OF MANAGEMENT, 2025)
The problems of UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan undergraduate graduates are: 1) The ratio of graduate acceptance in the job market is still low, namely 49.97% percent, 2) The waiting period for UIN Syahada Padangsidimpuan students after graduation still exceeds the maximum standard of 6 (six) months. 3) The condition of the integrated laboratory at UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan is still far from the standard of education services based on Government Regulation Number 57 of 2021 concerning National Education Standards. As a solution to this problem, it is important to improve the quality of facilities, infrastructure and learning at UIN Syahada Padangsidimpuan. The development of laboratory facilities and infrastructure at UIN Syahada is a very important policy in overcoming problems and improving the quality of education in meeting educational service standards at UIN Syahada Padangsidimpuan.